Peningkatan Kapasitas Jalan Dengan Melihat Penurunan Parameter Data LHR dan VCR Akibat Covid-19: Studi kasus: Ruas Tanjung Kemuning – Linau dari Desa Kasuk Baru (STA 208+305) Sampai Dengan Desa Sedaya Baru (STA 218+500) - Wahyudi, Riski (JOURNAL INFORMATION TECHNOLOGY ENGINEERING AND SCIENCE, 2022)
Kaur Regency in Bengkulu Province which has the capital city in Bintuhan by looking at the level of population and economic development, currently the capacity of the main road in the center of the district capital with the status of a national road is already less able to accomodating the capacity of the existing traffic rate. For this reason, it is necessary to improve the road structure through road widening. However, data support as a reference in road widening such as LHR and VCR show a decrease due to the Covid-19 force majeure from 2019 to 2022. So it is necessary to do an analysis because the road conditions are returning to normal which shows the volume of heavy traffic as an indication of the need improvement of the road structure.